Teamwork Analysis on Improving Employee Performance at Kemang Jaya Restaurant 2 - Kodratullah, Muhammad Lintar; Syahreza, Dina Sarah; Aprinawati, Aprinawati; Putri, Nada Deliza; Napitupulu, Putra Jhonatan Mula Jaya; Sianturi, Reni Marlina; Sinaga, Mhd Fadillah Ilham (Economic: Journal Economic and Business, 2025)
This study analyzes the effect of teamwork on employee performance at Kemang Jaya 2 Restaurant using a qualitative approach. The results of the study indicate that effective teamwork, supported by good communication and inclusive leadership, has a positive impact on increasing employee productivity and job satisfaction. However, challenges such as work discipline and interpersonal conflict are still obstacles that need to be managed strategically. The recommendations of this study include communication training, conflict management, and collaborative skills development to create a more conducive work environment. With this strategy, it is hoped that organizations can improve operational effectiveness and competitiveness in the competitive restaurant industry.